Análise combinatória: uma abordagem diferenciada sem a utilização de fórmulas - Roda, Thiago Miguel (2018)
In view of the difficulties encountered in the teaching of Combinatorial Analysis in public schools, both the student and the teacher of the High School, the present work has gained form to propose a differentiated approach. The work aims to approach Combinatorial Analysis without the use of formulas, because it has been perceived that Combinatorial Analysis is treated by many as a branch of Mathematics that needs to decorate formulas, mechanizing students' learning. With this, the content is titled as one of the most difficult in Mathematics, so we propose to work only with the Fundamental Principle of Counting (PFC) as a tool of the resolutions of the exercises. We worked on the proposal in practice with a high school room, and we get very good results. We hope that the study will be a material for studies of teachers and students.